ANALISIS PENGARUH CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NPM (Net Profit Margin), ROA (Return On Asset), LDR (Loan to Deposit Ratio) TERHADAP KINERJA KEUANGAN PERBANKAN YANG LISTING DI BEI (2007-2011) - Anita, Yulia; Fitrios, Ruhul; L, Al-azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to empirically study effect of CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NPM (Net Profit Margin), ROA (Return On Asset), LDR (Loan to Deposit Ratio)to the financial performance of banks on the Indonesian Stock Exchange. This research was conducted with a popolatian 21 and purposive sampling method against 16 banking companises in the indonesia stock exchange in the period 2007-2011. Analysis on the data obtained in the form quantitative analysis. Methode in this study using multiple regression analysis. The results of this study showed that NPL variable, NPM, ROA affect the financial performance of banks is measured by profit growth, while the CAR and LDR doesn’t affect the bsnk’s financial performance is measured by profit growth.Keywords: profit growth, CAR, NPL, NPM, ROA, LDR